CONSERVATION OF THE RED - SHANKED DOUC LANGURS (Pygathix nemaeus) IN BACH MA NATIONAL PARK: AN UPDATE ON DISTRIBUTION AND POPULATION SIZE - Van Minh, Nguyen (Journal of Forestry Science and Technology, 2019)
The red-shanked douc langur Pygathix nemaeus is a rare and endangered primate species endemic to Vietnam, Lao PDR and Cambodia. The red-shanked douc langurs were previouly found in Bach Ma National Park and their population has been mainly recorded in the northeastern Park, however, there is still a lack of information about distribution and population status in the southwestern Park. To improve conservation prospects of the species there, the present study aims to update the database on distribution and population status of the red-shanked douc langurs in Bach Ma National Park, Thua Thien - Hue province. The line transect surveys were carried out from 14 lines in Bach Ma National Park in 2018 - 2019. The results showed that 08 groups of the red-shanked douc langurs were recorded in the areas of Bach Ma National Park. The population size was estimated around from 68 to 86 individuals. The number of groups and population size of the red-shanked douc langurs recorded in the present study is larger than that in the previous reports. Two groups of the red-shanked douc langurs were recorded for the first time in the southwestern area of Bach Ma National Park. The habitats of this species in Bach Ma National Park mainly occur in the rich and medium forests of evergreen broad-leaved forest (TXG and TXB) and were recorded at the elevations from 500 m to 1,400 m above sea level. The present study has identified 04 main threats affecting the habitats and red-shanked douc langurs in Bach Ma National Park, including hunting, illegally exploiting forest products, development of tourisms supported by road constructions and buildings, and conversion of forest into agricultural land and acacia plantations, among which illegal hunting is the most serious threat to the red-shanked douc langurs in the study area.